Case Report: Molecular Characterization of Aggressive Malignant Retroperitoneal Solitary Fibrous Tumor: A Case Study - Nonaka, Haruna; Kandori, Shuya; Nitta, Satoshi; Shiga, Masanobu; Nagumo, Yoshiyuki; Kimura, Tomokazu; Kawahara, Takashi; Negoro, Hiromitsu; Hoshi, Akio; Kojima, Takahiro; Kawai, Koji; Mathis, Bryan J.; et al. (Frontiers in Oncology, 2021)
Solitary fibrous tumors (SFT) are mesenchymal neoplasms with a favorable prognosis usually originating from the visceral pleura. Rarely, they may occur at various extrapleural sites and show malignant behavior coupled with dedifferentiation. NAB2-STAT6 fusion gene and STAT6 nuclear expression are biomarkers for diagnosis of SFT in addition to CD34, Bcl-2, and CD99. Furthermore, several reports have shown specific NAB2-STAT6 fusion variants and loss of STAT6 protein expression are associated with malignancy. We report a rare case of retroperitoneal SFT which rapidly progressed to death within 35 days after admission. Autopsy found a primary tumor containing both benign and malignant histologies, with multiple metastatic sites similar to the malignant, dedifferentiated tumor. STAT6 was detected in the primary differentiated tumor but not in the primary dedifferentiated tumor or lung/liver metastases. However, the NAB2-STAT6 fusion gene (NAB2ex6/STAT6ex16 variant) was detected in the primary tumor and lung/liver metastases. Intriguingly, fusion gene expression at the transcriptional level was downregulated in the dedifferentiated tumors compared to the differentiated tumor. We further performed target DNA sequencing and found gene mutations in TP53, FLT3, and AR in the dedifferentiated tumors, with TP53 mutations especially found among them. We demonstrate that downregulation of NAB2-STAT6 fusion gene at the transcriptional level is associated with malignant SFT for the first time. Moreover, the present study supports the idea that TP53 mutations promote malignancy in SFTs.